UPAYA MENINGKATKAN PRESTASI BELAJAR MATEMATIKA DENGAN METODE COOPERATIVE SCRIPT - Ika Septi Hidayati; Dita Weardani (Intersections, 2020)
The purpose of this study was to determine the appropriate application of the cooperative script method in order to improve the learning achievement of the fifth grade students of SD Negeri Prembulan. The results of this study indicate that: (1) In general the application of the appropriate cooperative script method is effective in improving mathematics learning achievement, (2) The increase in mathematics learning achievement of the fifth grade students of SD Prembulan in the pre-cycle is 65.07 in the first cycle of 78, 31 in cycle II of 86.39